TPH, SLC6A2, SLC6A3, DRD2 and DRD4 Polymorphisms and Neuroendocrine Factors Predict SSRIs Treatment Outcome in the Chinese Population with Major Depression - Yin, L.; Zhang, Y. Y.; Zhang, X.; Yu, T.; He, G.; Sun, X. L. (Pharmacopsychiatry, 2015)
Objective: This study was intended to determine whether antidepressant outcome to SSRIs was associated with catecholamine gene polymorphisms and neuroendocrine factors in patients of Chinese Han ethnicity with MDD.Method: A total of 290 MDD patients were recruited and received a 6-week randomized double-blinded treatment. Cortisol, adrenocorticotropic hormone (ACTH), thyroid-stimulating hormone (TSH), 3′-triiodothyronine (T3), thyroxine (T4), free triiodothyronine (fT3), and free thyroxine (fT4) levels were measured at the baseline. Allele, genotype, and haplotype frequencies of catecholamine genes were compared between responders and non-responders, remission and non-remission groups respectively.Results: We found that genotype frequency of the rs1800544 polymorphism in the DRD4 gene was significantly different between responders and non-responders (P<0.05). Also the frequency of the rs1800544 CG genotype was significantly higher (P<0.05) in responders (51.4%) than that in non-responders (35.8%). No significant difference was found between responders and non-responders, remission and non-remission groups in the SNPs polymorphisms in the TPH, SLC6A2, SLC6A3, or DRD2 genes. The combination of all neuroendocrine factors, clinical characteristics and gene polymorphisms predicted 74.8% of the variation in SSRI response and 65.5% in SSRI remission.Conclusion: Polymorphisms of the DRD4 gene were associated with SSRI response in Chinese Han MDD patients. A combination of clinical characteristics, neuroendocrine factors, and gene polymorphisms might be able to predict the outcome to SSRIs.
Keywords: depression; neuroendocrine factors; genes; DRD4; pharmacogenetics